Scale development and validation to measure student's perceived impact of learning and satisfaction towards e-learning / Nursyahida Zulkifli, Nor Raihana Asmar Mohd Noor and Nor Farizah Johari - Zulkifli, Nursyahida; Mohd Noor, Nor Raihana Asmar; Johari, Nor Farizah (Universiti Teknologi MARA, 2022)
The educational system across the world has greatly been affected due to outbreak of COVID-19; it forced the closure of educational institutions to prevent the spread of the virus. Due to that, all teaching and learning programmes should be conducted through online platform. Hence, the presence of e-learning, computer-based learning has emerged as closest substitute for off-line teaching. Thus, the purpose of this study is to establish a standardised measurement that engender satisfaction and positive impacts of e-learning. To develop and validate the scale, a sequential process is conducted which includes item generation, item purification and item validation. Relevant literature was reviewed and responses from 164 students of Universiti Teknologi MARA, Kelantan's Campus, Malaysia were collected through online questionnaire to explore the factor structure and to validate the scale. Confirmatory factor analysis (CFA) using SmartPLS (version 3.3.3) was used to validate the scale. The findings of the study recommend the extension of the scale development and validation used in this research for future research. The findings of the study will facilitate educational institutions and policy makers to take this online-learning process to the next level in a better way.